The Norwegian and Danish Negative Expressives and Their Czech Translations - Pavel Dubec; Radka Stahr (Acta Universitatis Carolinae: Philologica, 2025)
The present article explores the use of negative expressives in Danish and Norwegian, examining their semantic categories and how they are translated into Czech. It focuses on the preservation of the negative value in the translation, analyzing whether the intensity or negative connotation is adequately conveyed. The study also touches on the role of negative expressives as intensifiers, Anglicisms, and the presence of idiomatic expressions in both the source languages and the translation. By comparing these elements, the article provides some insights into the linguistic and cultural nuances involved in translating negative expressives from Danish and Norwegian into Czech.